Pemberdayaan Kinerja Museum Melalui Kegiatan Seni dalam Mendukung Branding Museum dan Galeri Seni SBY*Ani - Nur Rahmat Ardi Candra Dwi Atmaja; Fawarti Gendra Nata Utami (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The creative economy sector is increasingly gaining public interest as a primary source of livelihood. This is evidenced by the proliferation of creative products marketed through digital platforms. The integration of the Creative Economy Agency into the Ministry of Tourism and Creative Economy demonstrates the government's ongoing commitment to making this sector a strategic priority. Museums function as information centers equivalent to libraries, storing and presenting knowledge through their collections, thus serving a dual role: tourist destinations and educational spaces. Both serve parallel functions as sources of information, documentation tools, scientific research facilities, and carry out classification, inventory, and preservation processes, despite fundamental differences behind these similarities. Promotional strategies have now evolved beyond print media, utilizing audio, visual, and audiovisual formats, particularly through social media, to the creation of various forms of arts activities. The SBY*ANI Museum and Gallery are currently optimizing social media as a promotional or branding instrument to increase the number of public visits to the museum. The development of creative and innovative models or forms of arts activities that can continue to emerge and be present sustainably is crucial. The SBYANI Museum and Gallery have strategic potential as a vehicle for history and arts education in Indonesia. However, amidst the digital transformation, this institution faces complex challenges: low appeal to the younger generation and weak branding in the public sphere. Through a community service program, this initiative is designed to revitalize the museum through a series of arts activities. These activities include contemporary art exhibitions, multidisciplinary performances, and collaborations with creative communities.